Diccionario de peruanismos de Juan de Arona: ideas político-lingüísticas (siglo XIX) - de la Cruz Espinoza, Arthur Ramón (2025)
This article discusses the influence of 19th-century political and linguistic ideas from Europe on the lives of the newly emancipated republics of Latin America, particularly in the lexicographical production of that century. A representative example of the need for coherence between political-linguistic ideas in Europe and America is Juan de Arona’s Diccionario de peruanismos, in which, with a conservative perspective, he not only underestimated the linguistic ingenuity of Peruvian speakers but also deplored any “form” that did not adhere to the Iberian norm. As demonstrated in this article, this viewpoint is clearly reflected over time in his Diccionario de peruanismos, where ideas of purism, unity of Spanish, and idealized language uses take precedence over the actual language practices and innovations of Peruvian speakers.